(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years, social media plays a major role in user decisions using reviews, feedbacks. This allows everyone to leave a review, creating a prime opportunity for spammers to write spam reviews about goods and services of various interests. Trending Research Area: Identifying these spammers and the spam material is a key subject of study, and while a significant number of studies have recently been conducted to this end, the methodologies put forward so far barely identify spam feedback, and none of them demonstrate the value of each derived function category. Every spam detector system fails to identify this kind of spammers or at least has some trouble to spot them. In our proposed system, we analyse two categories effectively named review-behavioral and user-behavioral to identify spam reviewers. Using the available web services, we are going to build this application and provide efficient accuracy in detecting spam reviewers in social media forums.